Comparison of polyphenols, anthocyanins and color analysis in pigmented maize from northeast Mexico - Josué I. GARCÍA-LÓPEZ; Eduardo HERNÁNDEZ-ALONSO; Antonio FLORES-NAVEDA; Sait JUANES-MÁRQUEZ; Sonia RAMÍREZ-BARRÓN; Agustín HERNÁNDEZ-JUÁREZ; Neymar CAMPOSECO-MONTEJO; Perpetuo ÁLVAREZ-VÁZQUEZ (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2025)
This work aims to evaluate and compare the chromatic characteristics, mineral concentration, and phenolic compound content (total phenols, total flavonoids, anthocyanins, and condensed tannins), as well as antioxidant capacity levels (DPPH, ABTS, and FRAP) in maize genotypes with white, yellow, orange, and blue/purple grain pigmentations. The results showed that the lightness, colour saturation, and hue angle (L*, C*, and h°) values ranged from 25.33 to 69.15, 1.51 to 32.22, and 32.38 to 92.07, respectively. All the maize varieties studied showed a high concentration of N, P, K and Mg. In the case of Fe, Mn, Zn and Cu, lower values were obtained with ranges of 2.18 to 3.01, 0.43 to 0.79, 1.61 to 2.43 and 0.08 to 0.42, respectively. The content of total phenols and flavonoids (free + bound) was in a range of 236.11 to 1296.16 mg GAE/100 g, and 29.20 to 221.22 mg CE/100 g, respectively, showing that the bound fractions were higher than the free fractions. Condensed tannins were only found in pigmented maize varieties in the free fraction, with values ranging between 46.58 and 411.87 mg CE/100 g, while the concentration of total anthocyanins ranged between 1.15 and 265.61 mg C3GE/100 g. Finally, the antioxidant capacity (free + bound) expressed in μmol TE/100 g was from 870.37 to 10763.34 for DPPH, from 1396.10 to 10895.26 for ABTS, and from 634.95 to 2185.92 for FRAP, with mean values of 6.5 mg/mL for the IC50 in DPPH and ABTS. A negative correlation was found between the total phenol content and the color parameters L*, C* and h°, indicating that red and purple maize grains presented the highest levels of antioxidant compounds.